Number 25 (March 1992) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1992)
(March 1992) - Water Currents in Spawning Areas of Pebble Nests of Nocomis leptocephalus (Pisces: Cyprinidae). By E.G. Maurakis, et al., 3 pp. Minutes, Regional Reports and News Notes.
Keywords: water currents; spawning; pebble nests; nocomis leptocephalus